Tellurium Compounds Prevent and Reverse Type-1 Diabetes in NOD Mice by Modulating α4β7 Integrin Activity, IL-1β, and T Regulatory Cells - Yossipof, Tom Eitan; Bazak, Ziva Roy; Kenigsbuch-Sredni, Dvora; Caspi, Rachel R.; Kalechman, Yona; Sredni, Benjamin (Frontiers in Immunology, 2019)
The study shows that treatment of NOD mice with either of two tellurium-based small molecules, AS101 [ammonium trichloro(dioxoethylene-o,o')tellurate] or SAS [octa-O-bis-(R,R)-tartarate ditellurane] could preserve β cells function and mass. These beneficial effects were reflected in decreased incidence of diabetes, improved glucose clearance, preservation of body weight, and increased survival. The normal glucose levels were associated with increased insulin levels, preservation of β cell mass and increased islet size. Importantly, this protective activity could be demonstrated when the compounds were administered either at the early pre-diabetic phase with no or initial insulitis, at the pre-diabetic stage with advanced insulitis, or even at the advanced, overtly diabetic stage. We further demonstrate that both tellurium compounds prevent migration of autoimmune lymphocytes to the pancreas, via inhibition of the α4β7 integrin activity. Indeed, the decreased migration resulted in diminished pancreatic islets damage both with respect to their size, β cell function, and caspase-3 activity, the hallmark of apoptosis. Most importantly, AS101 and SAS significantly elevated the number of T regulatory cells in the pancreas, thus potentially controlling the autoimmune process. We show that the compounds inhibit pancreatic caspase-1 activity followed by decreased levels of the inflammatory cytokines IL-1β and IL-17 in the pancreas. These properties enable the compounds to increase the proportion of Tregs in the pancreatic lymph nodes. AS101 and SAS have been previously shown to regulate specific integrins through a unique redox mechanism. Our current results suggest that amelioration of disease in NOD mice by this unique mechanism is due to decreased infiltration of pancreatic islets combined with increased immune regulation, leading to decreased inflammation within the islets. As these tellurium compounds show remarkable lack of toxicity in clinical trials (AS101) and pre-clinical studies (SAS), they may be suitable for the treatment of type-1 diabetes.